2020
DOI: 10.1108/jkm-11-2019-0675
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge spillover driven by institutions: evidence from the big science project in China

Abstract: Purpose This study aims to explore the knowledge spillover mechanism in big science projects (BSP) from an institutional perspective by elaborating on the dynamic relationship between institutional dualism and legitimacy. Design/methodology/approach The study conducts an exploratory research and adopts the grounded theory methodology in the context of BSP. Data draw mainly upon nine semi-structured interviews. Findings The knowledge spillovers in BSP are driven by institutions, which work through mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Gao and Guan (2012) proposed a network model based on citation time series, which integrated the methods of time series networks, epidemic spread models, main path analyses and characterized the main path and overall speed of knowledge diffusion. Zhang et al (2021) explored the knowledge spillover mechanism in big science projects (BSP) from an institutional perspective, and they found the knowledge spillover in BSP was driven by institutions. Huang et al (2021) developed a two-layer network to model the interaction between the spread of epidemic and the competitive diffusions of information.…”
Section: Related Workmentioning
confidence: 99%
“…Gao and Guan (2012) proposed a network model based on citation time series, which integrated the methods of time series networks, epidemic spread models, main path analyses and characterized the main path and overall speed of knowledge diffusion. Zhang et al (2021) explored the knowledge spillover mechanism in big science projects (BSP) from an institutional perspective, and they found the knowledge spillover in BSP was driven by institutions. Huang et al (2021) developed a two-layer network to model the interaction between the spread of epidemic and the competitive diffusions of information.…”
Section: Related Workmentioning
confidence: 99%
“…Second, this study places carbon transfer and technology spillovers within a carbon policy framework. Previous studies have been limited to exploring the directions and measurements of carbon transfers (Dong et al , 2022; Ji et al , 2020), or productivity and product quality improvement caused by technology spillovers (Zhang et al , 2021). The importance of carbon transfers and technology spillovers should be reexamined, since carbon emission rights are regarded as commercial resources (Sun and Zhong, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Kecskes and Nguyen (2021) argued that technology spillovers could help enterprises adopt flexible financial policies while increasing their value to other enterprises. Zhang et al (2021) found that sharing technology achievements could help stakeholders achieve progress in research and development by exploring technology spillover mechanisms. These scholars have focused on the direct benefits, such as lower production costs, higher product quality and higher productivity levels, of technology spillovers.…”
Section: Research On Supply Chain Decisions In the Presence Of Techno...mentioning
confidence: 99%
“…From an institutional perspective, KSs can be driven by institutions (Zhang et al, 2021). Domestic firms may imitate the CSR reporting practices of foreign firms to meet the requirements of regulations (Muller & Kolk, 2010).…”
Section: Foreign Ownership Csr Reportingmentioning
confidence: 99%
“…External pressures, especially institutional pressures, are key determinants of passive‐learning KSs. Formal and informal institutions “influence organizational and individual behavior through legitimacy pressure and support” and encourage KSs (Zhang et al, 2021). In contrast, nonpassive‐learning spillovers are KSs in forms other than passive‐learning spillovers.…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%